Spatiotemporal Distribution and Driving Force Analysis of the Ecosystem Service Value in the Fujiang River Basin, China - Zhang, Xuemao; Xie, Binggeng; Li, Junhan; Yuan, Chuan (Land (Basel), 2023)
Identification of spatiotemporal changes in ecosystem service value and their drivers is the basis for ecosystem services management and decision making. This research selects Fujiang River Basin (FJRB) as the area of study, using the equivalent factor method to estimate the ecosystem service value (ESV) variation and characteristics of its spatial distribution. The contributions of the drivers of ecosystem service value and their interactions were also explored using the optimal parameters-based geographical detectors (OPGD) model. The results showed the following: (1) the total ESV increased from 104,891.22 × 106 yuan to 105,032.08 × 106 yuan from 2000 to 2020, and displayed an upward trend from the southeast to northwest; (2) The distribution of ESV showed a strong positive spatial autocorrelation. High ESVs were concentrated upstream of the study region with a higher elevation and vegetation coverage, whereas low values were mainly found in the midstream and downstream regions, where frequent human activity occurs; (3) The elevation of natural factors, HAI and LA of human-social factors, and PEL of landscape pattern factors were the main forces leading to ESV differentiation, and the spatial heterogeneity of ESV in the study area resulted from the synergistic effect of natural factors, human socioeconomic activities, and landscape pattern factors. This research reveals the spatial and temporal patterns and drivers of ecosystem service values in the FJRB, and provides a scientific reference for the establishment of land-use planning and ecological environmental protection mechanisms in this region.